Enhancing livestock investments for climate-resilient and inclusive policy implementation - Wong, Madeline (International Livestock Research Institute, 2023)
Last month, the CGIAR Research Initiative on Sustainable Animal Productivity (SAPLING) and Livestock and Climate (LCSR) led by International Livestock Research Institute (ILRI) collaborated with the Botswana University of Agriculture and Natural Resources (BUAN) to host the side event, ‘Enhancing livestock investments: policies, strategies, and partnerships for sustainable livelihoods in Africa at the All-Africa Conference on Animal Agriculture (AACAA8) in Gaborone, Botswana. This event called for increased collaboration between diverse stakeholders on policy and strategy support and sustainable development. A collaborative, enabling environment will unlock investment opportunities to better implement solutions towards a more climate-resilient, inclusive livestock sector for the continent.